Literatur Review Kualitas Tidur Lansia Dengan Tekanan Darah Pada Pasien Hipertensi - Rasmanah Rasmanah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Hypertension is a measurement of systolic blood pressure of more than 140 mmHg or diastolic blood pressure of 90 mmHg and the measurement is more than 2 times. The purpose of this literature review is to determine the relationship between elderly sleep quality and high blood pressure in hypertensive patients based on the literature review. Writing this journal uses a literature study approach from several search databases from pubmed and proquest with the last 5 years of publication (2017-2022). Keywords used are sleep quality, elderly, and hypertension. The literature study showed that from 10 journals studied, there was a relationship between sleep quality and hypertension from several factors, including sleep duration <6 hours, frequent awakenings at night, illnesses suffered and the elderly experienced nocturia. Where nocturia is someone who often urinates excessively at night. In conclusion, from 10 articles that show a significant relationship, it has been analyzed that sleep quality is related to hypertension, but poor sleep quality can be caused by several triggering factors including sleep duration > 6 hours, illnesses such as diabetes mellitus, and hyperlipidemia, and sleep quality. in women aged > 60 years and over more often experience nocturia so that the quality of sleep decreases.